Study on the preparation and luminescence properties of SrGe4O9:Mn4+ red phosphors for plant illumination. Issue 4 (17th March 2023) - Zhao, Li; Wenjia, Dang; Ya‐nan, Wang; Kun‐yao, Wu; Ming, Sun
Abstract: In this study, SrGe4 O9 :Mn 4+ red phosphors for plant illumination were prepared using a high‐temperature solid‐phase method. The samples were characterized and analyzed by X‐ray diffraction (XRD), field emission scanning electron microscopy (FESEM), fluorescence spectroscopy, and other techniques. The phase structure, apparent morphology, and luminescence properties of the SrGe4 O9 :Mn 4+ red phosphors were investigated. The results indicated that the dopant Mn 4+ was incorporated into the matrix structure by substituting some Ge 4+ ions without any changes in the crystal structure of the SrGe4 O9 matrix. The samples comprised micron‐scale particles and exhibited high purity and uniform distribution of elements. The SrGe4 O9 :Mn 4+ phosphors exhibited relatively strong red light emission at 660 nm under the excitation of a 430‐nm blue light, and the luminescence intensity was the highest when the Mn 4+ doping amount was 1%. Proper doping of Ti 4+ or Sn 4+ could effectively improve the luminescence intensity of the SrGe4 O9 :Mn 4+ phosphors. The light‐emitting diode (LED) device packaging showed that the SrGe4 O9 :Mn 4+ red phosphors could be used for plant growth illumination. Abstract : The LED devices successfully obtained after drying were tested with a Hongpu HP9000 spectral color illuminometer.